THE ROLE OF INTEGRATED ISLAMIC COMMERCIAL AND SOCIAL FINANCE IN REDUCING INCOME INEQUALITY IN INDONESIA - Arif Widodo (Journal of Islamic Monetary Economics and Finance, 2019)
Recent years saw the heated debates among prominent economists on the growing inequality in advanced economies, and accordingly, many solutions to this serious problem have been put forward. Among the practical-cum-workable solution is progressive taxation for wealth and income, especially the top one percent. Such a solution, however, has been implemented in Islamic perspective what so-called, zakah which is now referred to as social finance. In this paper, using the Gini coefficient data covering 34 provinces in Indonesia over a decade, we examine whether the role of social finance in tandem with commercial finance can adequately solve the problem of wealth distribution in Indonesia, one of the largest Democratic-Muslim countries in the world. Using the Generalized Method of Moments (GMM) model, the results demonstrated that Islamic commercial finance solely is proven statistically incapable of tackling inequality while the social finance (zakah) is performing very well in this matter over all specifications. Most importantly, when both are incorporated in a model, the result showed a significant reduction in income inequality implying that the integrated Islamic finance which can be implemented in both Islamic microfinance institution and Islamic banking is more capable, as opposed to when both are separated, of helping address the income inequality problem in Indonesia.